PENGARUH KARAKTERISTIK DEWAN TERHADAP ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DISCLOSURE (Studi Empiris pada Perusahaan yang Terdaftar di Indeks Kompas 100 Bursa Efek Indonesia Tahun 2021-2023) - Thival Alvahlevi; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the influence of board characteristics on Environmental, Social, and Governance (ESG) disclosure. The board characteristics studied include board size, board gender diversity, proportion of independent boards, and frequency of board meetings. In addition, this study also uses control variables in the form of company size, liquidity, and leverage.The sampling method was carried out using purposive sampling technique, so that 38 companies were obtained as samples with a total of 114 observations during the 2021-2023 period. The data used is secondary data obtained from financial reports, company annual reports, and financial reports on companies incorporated in the Kompas 100 Index on the Indonesia Stock Exchange (IDX). Data analysis was carried out using multiple linear regression with the help of SPSS 25 software.The results showed that board size has a negative and significant effect on ESG disclosure, while board gender diversity and the proportion of independent boards have a positive and significant effect. The frequency of board meetings does not show a significant effect. The findings are expected to contribute to the literature related to corporate governance as well as be a consideration for stakeholders in encouraging better ESG disclosure.